Moving beyond quality-adjusted life-years in elderly care: how can multicriteria decision analysis complement cost-effectiveness analysis in local-level decision making - Hoedemakers, M; Tsiachristas, A; Rutten-van Mölken, M (Elsevier, 2022)
Objectives: This study aimed to investigate how multicriteria decision analysis (MCDA) could complement cost-effectiveness analysis (CEA) to support investment decisions in elderly care at local level.